Balanço ambiental de elementos-traço na sinterização - Lucas Ladeira Lau (2015)
Introduction: Environmental legislation is becoming more restrictive in several industrial sectors, especially in the steel industry, which is well known for its large pollution potential. With the recent growth of interest in the effects of trace elements on the environment and health, the inclusion of emission limits for these elements in this legislation has become increasingly popular. This article aims to describe the partitioning of trace elements between the products (sinter) and plant emissions in an iron ore sinter plant, aiming to better understand the behavior of these elements in the sintering process to eventually support interventions to modify these partitions. Methods: This was an experimental study in which, initially, the chemical characterization of several sintering inputs was initially performed. Based on the trace elements concentrations, we analyzed the injection of them in a sintering pilot using a sintering mixture. Mass balance was then used to determine the theoretical partitioning of trace elements in the sinter and emissions. After the mass balance, a volatilization study was carried out. In this study six sinter feed samples of different origins were selected and then a simulation of the sintering heating curve was performed in a radiant oven. With the chemical characterization of the samples before and after being subjected to heating, the tendency of each element to volatilize during the sintering process was determined. Results and Discussion: Regarding the chemical characterization of sintering inputs, it reveals that the steel-making residues contained large concentrations of trace elements, whereas low concentrations were observed in the flux. As to the mass balance, cadmium, nickel, lead, mercury, and copper exhibited greater tendencies to concentrate in atmospheric emissions. It was also observed that, although they are not, in general, major hubs of trace elements, ferrous inputs (sinter feed, pellet feed and others) have great relevance in the contribution of trace elements to the process, as they represent a great part of the mass of inputs used in the sintering mix. Meanwhile, the volatilization test showed which of the elements have the tendency to volatilize. For some elements the result was inconclusive. Conclusion: The ferrous raw materials, especially the sinter feed, are mainly responsible for the inputs of trace elements in the sintering system, and these same inputs, when original from Brazil or South Africa, have lower concentrations of these elements when compared to the ones with Chinese, Indian and Australian origins. The study of the behavior of trace elements in sintering is very complex since the same element may behave in three different ways depending on the phase it is located. The elements and compounds that have lower vaporization temperatures should volatilize and concentrate on the emissions. Moreover, elements that do not volatilize during the process can remain in the mixture and form the sinter, or they can become a part of emissions through the drag of the particles. Therefore, knowing the behavior of trace elements in the sintering process is of fundamental importance for the prevention of emissions and optimization of the processes in the steel industry.